Case Report: A rare case of familial progressive cholestasis type 10 in an adult with heterozygous MYO5B variant - Huimin, Zhang; Yuan, Wang; Chuanyan, Xu; Jing, Chen (Frontiers in Gastroenterology, 2025)
Progressive familial intrahepatic cholestasis (PFIC) is a group of rare autosomal recessive cholestatic liver diseases that typically manifest in infancy or childhood. It is characterized by intrahepatic cholestasis, jaundice, pruritus, and malabsorption, with potential progression to cirrhosis, liver failure, and hepatocellular carcinoma. Here, we report a 36-year-old Chinese male patient with delayed-onset PFIC who presented with recurrent jaundice and pruritus. Laboratory investigations excluded viral, autoimmune, or neoplastic causes of liver injury. Liver biopsy demonstrated hepatocyte hydropic degeneration and intracanalicular bile thrombi, while genetic testing revealed compound heterozygous variants in the MYO5B gene: c.3604-1G>C and c.1165G>T (p.V389F). The patient exhibited fluctuating bilirubin levels refractory to initial therapies including corticosteroids, ursodeoxycholic acid, cholestyramine, and artificial liver support. However, bilirubin normalization was achieved following adjunctive traditional Chinese medicine therapy after transfer to our institution. This case highlights that genetic etiologies, particularly MYO5B-related disorders, should be considered in patients presenting with recurrent hyperbilirubinemia, pruritus, and hepatosplenomegaly after excluding common causes (viral, autoimmune, drug-induced, or tumor-related). Genetic testing for MYO5B mutations is warranted in cases of high bilirubin with normal/mildly elevated GGT levels, as early recognition is critical for timely intervention.